Analyzing the power of collective agency in strengthening fisher communities in Kenya - FGDs - Gwada, Brenda; Adam, Rahma; Ndiema, Nicholas (2025)
This study aimed to explore group dynamics in fishing communities around Lake Victoria, Kenya. Using 17 Focus Group Discussions, information was gathered from group members, including linkage benefits, institutional mapping, vision strategies, gender participation, and access to finance.